Dysphonia caused by inhaled steroids: recognition of a characteristic laryngeal abnormality. Issue 11 (November 1983) - Williams, A J; Baghat, M S; Stableforth, D E; Cayton, R M; Shenoi, P M; Skinner, C
Abstract : Nine of 14 asthmatic patients who presented with persistent dysphonia while taking inhaled corticosteroids had a bilateral adductor vocal cord deformity with bowing of the cords on phonation. This causes the dysphonia and usually occurs without candidiasis. It was seen with beclomethasone dipropionate (in both pressurised aerosol and dry powder preparations), betamethasone valerate, and budesonide. It was related to the dose and potency of inhaled steroid and may represent a local steroid myopathy. It was reversed when the inhaled steroid was stopped, although resolution sometimes took weeks. Laryngeal candidiasis may have contributed to the vocal cord abnormality in two of these nine patients. Of the five patients without vocal cord deformity, laryngeal candidiasis was the sole cause of dysphonia in three. In the remaining two dysphonia was thought to be psychogenic. The vocal cord deformity may exist subclinically. Of nine patients who started to take aerosol steroid and who were examined monthly for one year, three developed vocal cord deformity but only one had persistent dysphonia. Vocal abuse did not appear to contribute to dysphonia.